Impact of wire sensor location on coronary physiological measurement. (14th October 2021) - Lotfi, A L; Haider, A H; Pervaiz, A P; Kadado, A J K; Bachman, M B; Rodriguez Arciniega, J R A; Visintainer, P V
Abstract: Background: The location of the wire sensor to measure FFR and dPR has not been systemically studied. Therefore, we hypothesize that the coronary physiological measurements will vary with the location of the sensor. This exploratory study is to assess whole cycle pressure distal/pressure aorta (Pd/Pa) ratio, FFR, and dPR at different sensor position within the vessel to evaluate the impact of pressure drop and measurements based on sensor position. Methods: 54 patients who had an indication for coronary angiography were screened and 30 consecutive patients were enrolled. The OptoWire 2 or 3 generation fiberoptic pressure wire was used to assess Pd/Pa, dPR, and FFR. Our primary goal is to test if those measurements vary with the FFR wire sensor placed at 10mm (proximal), 35–45mm (mid), and greater than or equal 60–70mm (distal) distal to the target lesion respectively. We used a multilevel linear regression approach. Results: Of 30 patients enrolled, 23 (76.6%) were males, mean age was 64.7 years (± 11.0 yrs), and mean stenosis was 61.6% (±13.4%). Adjusting for age, gender, and severity of stenosis, results showed that for all three measures (Pd/Pa, DPR, and FFR) (Figure 1), pressure decreased in a linear fashion the further the sensor was from the target lesion (p values <0.001). Further, pairwise comparisons of the measurements at adjacent locations similarly showed significant declines in pressure (p values <0.001). Conclusions: This is first study to demonstrate that the location of the pressure wire can impact the results of both resting and hyperemic pressures which can cause a false negative result. This is especially important where the values are near the cut-off. FUNDunding Acknowledgement: Type of funding sources: None.